2008
DOI: 10.1007/s00520-008-0484-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw (ONJ) in cancer patients treated with Bisphosphonates: how the knowledge of a phenomenon can change its evolution

Abstract: Bisphosphonates-related ONJ is a frequent adverse event (8.6%). The monitoring program proved very efficient to improve the clinical outcome of ONJ, avoiding an aggressive treatment and using a conservative approach and medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Although there is evidence that a preventative approach with oral evaluation, oral hygiene maintenance, and periodic follow-up under the supervision of dental professionals may decrease the number of cases of BON [14,25], the effectiveness of this evaluation in the prevention of BON needs to be demonstrated in well-designed trials.…”
Section: Discussionmentioning
confidence: 98%
“…Although there is evidence that a preventative approach with oral evaluation, oral hygiene maintenance, and periodic follow-up under the supervision of dental professionals may decrease the number of cases of BON [14,25], the effectiveness of this evaluation in the prevention of BON needs to be demonstrated in well-designed trials.…”
Section: Discussionmentioning
confidence: 98%
“…However, the majority of bisphosphonate studies only evaluated treatment for 2 years or less, with approximately 11%–36% of patients completing the studies and considered eligible for further treatment (Morgan et al., 2010; Rosen et al., 2003; Saad et al., 2004; Theriault et al., 1999). Few prospective and retrospective studies have reported on the efficacy and safety of bisphosphonate treatment beyond 2 years (Crawford et al., 2009; Dearnaley, Mason, Parmar, Sanders, & Sydes, 2009; Gnant et al., 2011; La Verde et al., 2008; Morgan et al., 2012). This small, prospective, observational study helps to confirm the safety and ongoing efficacy of monthly treatment with ZOL for 2–3 years in patients with malignant disease involving bone, in the era of new safety guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have shown that when patients were properly evaluated and monitored, the frequency of ONJ decreased significantly. [46][47][48] Dimopoulos et al 46 evaluated the rate of ONJ in 128 patients with multiple myeloma after the implementation of preventive measures. The rate of ONJ significantly decreased, and none of the patients developed stage III ONJ.…”
Section: Prevention and Treatment Of Onjmentioning
confidence: 99%
“…Another group of investigators evaluated 186 of their patients treated with bisphosphonates, 8.6% of whom developed ONJ. 47 The date of ONJ diagnosis was noted for each patient and classified into two groups: before and after implementation of preventive measures. Although no decrease in the rate of ONJ was found between groups, the patients who were diagnosed with ONJ after the preventive measures were undertaken had less severe symptoms and were successfully controlled and managed.…”
Section: Prevention and Treatment Of Onjmentioning
confidence: 99%